Metagenomic data on bacterial diversity profiling of Arabian sea sediment by amplicon sequencing - Nair, Harisree P. (Data Brief, 2019)
This data is about the microbial community genome analysis of Arabian sea sediment by Illumina sequencing by targeting the hypervariable region V3 of 16S rRNA gene. The data analysis revealed the existence of numerous unknown sequences, indicating a large unexploited bacterial diversity in the area. The raw sequence data used for analysis is available in NCBI under the Sequence Read Archive (SRA) with the BioProject No. PRJNA397165 and SRA accession number SRP125840.